Modelling company’s stock quotes under the economy’s cyclicity - Lyudmila I. Tenkovskaya (Journal of New Economy)
Economic and mathematical modeling and forecasting of company’s stock quotes are necessary for the formulation and successful implementation of trading strategies in stock markets. However, at present these processes do not always yield satisfactory results, since they are complicated by a lack of information and methods for studying the emerging trends in economic development. The paper aims at building second-order polynomial trend models of a company’s stock quotes to provide a corresponding forecast that allows for the economy’s cyclicity. Methodologically, the research relies on the fundamental propositions of the theory of economic cycles. The methods include time series analysis, economic and mathematical methods of modelling and forecasting. The data are quotes of Sberbank’s ordinary shares for February 1998 – August 2024 obtained from the financial portal Investing.com. Five polynomial trend models of quotes of Sberbank’s ordinary shares are built. According to them, the quotes of Sberbank’s ordinary shares will reach maximum levels in one and a half year. After the specified period, it is recommended to sell these investment assets. The findings can be also useful to investors and top managers when forecasting and assessing the probability of the new economic crises.